Representasi Matematis Siswa Tuna Rungu dalam Menyelesaikan Soal Cerita Matematika - Elis Dwi Wulandari; Erry Hidayanto; Rustanto Rahardi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: Mathematical representation is the way of communicating mathematical ideas and problems solutions. Communicating mathematical ideas requires external representation in the form of actions, verbal, symbolic, visual and real objects. This study aims to describe the form of representation of Deaf Students in solving mathematical story problems. The research was conducted by giving types of text questions as well as text and image questions to three DS at Banyuwangi State of Special Need High School. The results of student work analysis found that there are two types of mathematical representations that appear in solving story problems, namely verbal representation indicated by writing words, numbers, letters, sentences and oral and representation of mathematical expressions in the form of symbols and numbers. DS are able to representing, make mathematical symbols, explain in writing or sign language what they think are.Abstrak: Representasi matematis adalah cara mengomunikasikan ide-ide matematis maupun solusi permasalahan. Mengomunikasikan ide-ide matematis diperlukan representasi eksternal berbentuk tindakan, verbal, simbolik, visual dan objek nyata. Studi ini bertujuan untuk mendeskripsikan bentuk representasi siswa Tuna Rungu dalam menyelesaikan soal cerita matematika. Penelitian dilakukan dengan memberikan jenis soal teks serta soal teks dan gambar kepada tiga siswa TR di SMALBN Banyuwangi. Hasil analisis pekerjaan siswa ditemukan terdapat dua tipe bentuk representasi matematis yang muncul dalam menyelesaikan soal cerita, yaitu representasi verbal yang ditunjukkan dengan tulisan kata, angka, huruf, kalimat serta lisan dan representasi ekspresi matematis berupa simbol dan angka. Siswa TR mampu merepresentasikan, membuat simbol matematis, menjelaskan dengan tulisan maupun bahasa isyarat apa yang mereka pikirkan.